Spanish cities as filming locations: analysis and spatial distribution - Agustín Gámir Orueta; Patricia Montecino Huedo; Sergio Reyes Corredera (Boletín de la Asociación de Geógrafos Españoles)
The main objective of this article is to show the spatial distribution of Spanish cities according to the degree of their cinematographic projection. For this purpose, a sample consisting of 178 feature films was selected. After viewing each of them, 3,071 exterior clips from these movies were geo-localized. Using this methodology has enabled us to circumvent the feature film as a unit of analysis, and instead focus attention on the clips, understood as such as sequences shot in exteriors, with their precise duration and geo-localization. The article describes and differentiates between three large territorial areas for filming: the Autonomous Regions of Madrid, Spain’s coastal cities, and Spain’s interior cities, examining factors that explain the distribution of the shootings, whether geographic, cinematographic or administrative-economic. Information from the highest-rated movies reveals a group of Spanish cities with limited cinematographic dissemination, for which some recommendations are made for improving the projection of the city’s image.